Endosomal Toll-Like Receptors Mediate Enhancement of Interleukin-17A Production Triggered by Epstein-Barr Virus DNA in Mice - Shehab, Marwa; Sherri, Nour; Hussein, Hadi; Salloum, Noor; Rahal, Elias A. (Journal of virology, 2019)
Epstein-Barr virus is a pathogen that causes persistent infection with potential consistent viral DNA shedding. The enhancement of production of proinflammatory cytokines by viral DNA itself may contribute to autoimmune disease development or exacerbation. In this project, we identified that endosomal Toll-like receptors are involved in triggering proinflammatory mediators in response to viral DNA. Pathways and receptors involved may serve as future therapeutic targets for autoimmune diseases such as rheumatoid arthritis, multiple sclerosis, and systemic lupus erythematosus. We previously demonstrated that Epstein-Barr virus (EBV) DNA increases the production of the proinflammatory cytokine interleukin-17A (IL-17A) in mice. This property may contribute to the established association between EBV and autoimmune diseases. The objective of the present study was to elucidate mechanisms through which EBV DNA modulates IL-17A levels in mice. To determine whether endosomal Toll-like receptors (TLRs) played a role in this pathway, the expression of TLR3, -7, or -9 was assessed by real-time reverse transcription-PCR in mouse spleens after injection of EBV DNA. Moreover, specific inhibitors were used for these TLRs in mouse peripheral blood mononuclear cells (PBMCs) cultured with EBV DNA and in mice injected with this viral DNA; IL-17A levels were then assessed using an enzyme-linked immunosorbent assay. The expression of the endosomal receptors TLR3, -7, and -9 was increased in mice injected with EBV DNA. When mouse immune cells were cultured with EBV DNA and a TLR3, -7, or -9 inhibitor or when mice were injected with the viral DNA along with either of these inhibitors, a significant decrease in IL-17A levels was detected. Therefore, endosomal TLRs are involved in the EBV DNA-mediated triggering of IL-17A production in mice. Targeting these receptors in EBV-positive subjects with autoimmunity may be useful pending investigations assessing whether they play a similar role in humans. IMPORTANCE Epstein-Barr virus is a pathogen that causes persistent infection with potential consistent viral DNA shedding. The enhancement of production of proinflammatory cytokines by viral DNA itself may contribute to autoimmune disease development or exacerbation. In this project, we identified that endosomal Toll-like receptors are involved in triggering proinflammatory mediators in response to viral DNA. Pathways and receptors involved may serve as future therapeutic targets for autoimmune diseases such as rheumatoid arthritis, multiple sclerosis, and systemic lupus erythematosus.